Analisis Mutasi Gen SRY dan AZF serta Fungsi Gonad pada Penderita 46,XY Disorder of Sex Development (DSD) - Meira Erawati; Tri Indah Winarni; Ahmad Zulfa Juniarto; Ardy Santosa; Sultana MH Faradz (Fakultas Kedokteran Universitas Riau, 2011)
Disorder of sex development (DSD) includes congenital conditions in which development of chromosomal,gonadal or anatomy of urogenital is atypical. SRY and AZF genes have relationships with sex development andfertility in 46,XY DSD patients. Therefore, the condition of those genes and gonadal function on 46,XY DSD patientsare needed to be explored deeply. The aim of this study was to know the incident number of SRY and AZF genes andgonadal function of 46,XY DSD patients. So that it can be used as one of basic analyses of DSD and infertility statuson 46,XY DSD patients .Methods: This is an observational descriptive study with cross sectional approach. This study involved 36 patientsthat fulfilled the criteria of 46,XY DSD. The DNA of each sample was analyzed by PCR electrophoresis. The data ofhCG stimulation test were obtained from secondary data of patient’s medical record.Results: A hundred percent (100%) of 36 samples did not have deletion on their SRY gene. About 22,22% of sampleshad AZFa gene deletion especially on STS sY84. There were 19,44% samples that showed negative response to hCGstimulation test. Chi square test showed that AZFa deletion did not have relation with gonadal response positifity on46,XY DSD patients.Conclusion: Patients of 46,XY DSD need to be evaluated for their fertility especially on the sperm analysis afterreaching puberty period. It is done to patients with positive or negative gonadal responses to know whether infertilityis influenced by AZF gene or other factors.